2005
DOI: 10.1359/jbmr.050811
|View full text |Cite
|
Sign up to set email alerts
|

Growth Without Growth Hormone Receptor: Estradiol Is a Major Growth Hormone-Independent Regulator of Hepatic IGF-I Synthesis

Abstract: The role of estrogens in the regulation of pubertal growth independently of GH and its receptor was studied in male mice with disrupted GHRKO. E 2 rescued skeletal growth rates in GHRKO associated with an increase in hepatic and serum IGF-I. These data show that E 2 rescues pubertal growth during GH resistance through a novel mechanism of GHR-independent stimulation of hepatic IGF-I production.Introduction: Growth hormone (GH) and estrogen play a pivotal role in pubertal growth and bone mineral acquisition. Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 74 publications
7
50
1
Order By: Relevance
“…(24,34) Finally, more indirect AR-regulated mechanisms-including an impact on growth hormone secretion and its actions-may also be involved in the development of male cortical bone structure, a concept supported by observations of less cortical bone changes in male orchidectomized growth hormone receptor knockout mice. (35) In conclusion, in male mice, AR activation in osteocytes contributes to the decrease of trabecular bone but appears less or not important for the development of cortical bone during puberty.…”
Section: Discussionmentioning
confidence: 86%
“…(24,34) Finally, more indirect AR-regulated mechanisms-including an impact on growth hormone secretion and its actions-may also be involved in the development of male cortical bone structure, a concept supported by observations of less cortical bone changes in male orchidectomized growth hormone receptor knockout mice. (35) In conclusion, in male mice, AR activation in osteocytes contributes to the decrease of trabecular bone but appears less or not important for the development of cortical bone during puberty.…”
Section: Discussionmentioning
confidence: 86%
“…These findings indicated that sepsis reduced STAT5 phosphorylation and activity in liver as well as plasma IGF-1 following rhGH administration. The study by Venken et al (21) indicated that estradiol restored down-regulated receptor signaling systems, such as the estrogen receptor alpha and the prolactin receptor. Estradiol thereby recovered the JAK/ STAT pathway as evidenced by a significantly increased activation of the transcription factor STAT5.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used female rats, which mainly secrete estrogen. Estrogen is a major GH-independent regulator of hepatic IGF-1 synthesis (21). We assume that, in septic female rats, estrogen may increase activation of the transcription factor STAT5 and the hepatic IGF-1 gene transcription as well as plasma IGF-1 levels following rhGH administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the sex steroid hormones, several studies have shown that other hormones negatively regulated by estrogen, such as growth hormone (GH) and insulin-like growth factor 1 (IGF1), may further contribute to the development of the skeletal sexual dimorphism (Lupu et al 2001, Venken et al 2005, Callewaert et al 2010a. IGF1 levels are higher in males vs females during early puberty (Callewaert et al 2010b,c), and mice lacking GH receptor (GHR), IGF1, or both show a severe bone growth retardation (Lupu et al 2001).…”
Section: Sex Steroid Hormones Regulate Bone Growthmentioning
confidence: 99%